An Overview on the Recent Studies of Biochemic Remedies (Schüessler Tissue Salts) (Homoeopathy for All, 2025)
Background: Schüssler tissue salts, also known as biochemic remedies, were first introduced in the 19th century by Dr. Wilhelm Heinrich Schüssler. Based on 12 essential mineral salts considered critical for cellular function and overall health, these remedies aim to correct deficiencies that may lead to diseaseCurrent Use: Today, tissue salts are widely used across the globe, from managing growing pains in children to addressing joint stiffness in the elderly and aiding muscle recovery in athletes. They are commonly available in pharmacies, health stores, and online, particularly in Germany, Australia, India, and the UKResearch Gap: Despite their widespread popularity and anecdotal support, there is limited scientific research focused specifically on Schüssler salts. Most existing studies examine homeopathy more broadly rather than biochemic remedies. The available evidence largely consists of case studies and theoretical discussions, with only a few focused investigations, such as case studies on skin disorders, indicating possible therapeutic benefits.Conclusion: While Schüssler tissue salts remain an important complementary medicine system, there is a clear need for rigorous scientific evaluation through randomized controlled trials and mechanistic studies. This review aims to consolidate current findings and identify directions for future research.
Keywords: Schüssler; tissue; salts; biochemic; remedies